A Scientific Breakthrough technology to achieve conversion of Fructose which will result in toxic free sucrose and also conversion of Glucose to make low GI sucrose. (International Journal of Scientific Research and Management (IJSRM), 2016)
An Indian herbal technology to answer the world challenge to achieve toxic free sucrose and making sugar a low GI sucrose. The aim of the research is to convert Fructose and convert Glucose to achieve the above task. This will answer the alarming concern of sugar intake by the world population and also ease out the life of Diabetic world. The technology is designed with the power of organic engineering